A case report of massive pulmonary embolism in a pregnant woman with undiagnosed thrombophilia: Management strategies and timing for thrombophilia screening - Salma Bouyaddid; Yasmine Ouaddouh; Zakaria Bazid; Noha El ouafi; Nabila Ismaili (Radiology Case Reports)
Thromboembolic disease encompasses a wide range of disorders that include deep vein thrombosis and pulmonary embolism, within its clinical spectrum. The occurrence of pulmonary embolism in pregnant woman is a major cause of maternal mortality and presents significant management challenges, particularly when associated with thrombophilia. A condition characterized by an increased predisposition to thrombosis due to genetic defects. The rationale for screening remains a subject of debate and controversy. We present an uncommon case of massive pulmonary embolism with obstructive shock in a pregnant young woman testing positive for thrombophilia mutation. A female patient was admitted to emergency with symptoms of dyspnea and chest pain, clinical examination found signs of right ventricular insufficiency and hemodynamic instability. Transthoracic Echocardiography showed clear signs of massive pulmonary embolism with involvement of right cavities, paradoxal septum, McConnell sign; all improved after thrombolysis, resulting in excellent outcomes for both the pregnant woman and the fetus, that came out as a healthy newborn. The screening carried out away from the acute episode concluded for a mutation of factor V Leiden. In this case a timely diagnosis and a well-conducted screening for thrombophilic disorders increased the probability of survival for our patient and prevented other episodes of thrombo-embolism. Therefore, the quest to understand the etiology of embolism among young patients should be carried out, and more effort for thrombophilia screening must be assumed in a sensible, cost-conscious, evidence-based approach.